1997
DOI: 10.1021/la9620216
|View full text |Cite
|
Sign up to set email alerts
|

Structures and Dynamic Formation Processes of Porphyrin Adlayers on Iodine-Modified Au(111) in Solution:  In Situ STM Study

Abstract: The structures and dynamic formation processes of adlayers of 5,10,15,20-tetrakis(N-methylpyridinium-4-yl)-21H,23H-porphine (TMPyP) on both bare Au(111) and iodine-modified Au(111) in perchloric acid have been investigated in detail by using in situ scanning tunneling microscopy (STM). Highly-ordered TMPyP arrays formed on iodine-modified Au(111), whereas disordered adlayers were consistently found on bare Au(111) surface. High-resolution STM images revealed the characteristic internal shape and orientation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
135
1
4

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(157 citation statements)
references
References 45 publications
17
135
1
4
Order By: Relevance
“…Similar results were obtained by Itaya et al on the investigation of 5,10,15,20,-tetrakis-(N-methylpyridinium-4-yl) -21 H, 23 H-porphine tetrakis-(p-tolyenesulfonate) (TMPyP) on an iodine-modified Au (111) surface using ECSTM in a perchloric acid solution. [23,24] After the sample was annealed at 70 8C for 3 h, the STM results showed that arrangement II dominated the adlayer. Although domain I still existed, its percentage deceased remarkably, which indicated that the energy of arrangement II was lower than that of arrangement I, and that domain II was thus more stable.…”
Section: Resultsmentioning
confidence: 99%
“…Similar results were obtained by Itaya et al on the investigation of 5,10,15,20,-tetrakis-(N-methylpyridinium-4-yl) -21 H, 23 H-porphine tetrakis-(p-tolyenesulfonate) (TMPyP) on an iodine-modified Au (111) surface using ECSTM in a perchloric acid solution. [23,24] After the sample was annealed at 70 8C for 3 h, the STM results showed that arrangement II dominated the adlayer. Although domain I still existed, its percentage deceased remarkably, which indicated that the energy of arrangement II was lower than that of arrangement I, and that domain II was thus more stable.…”
Section: Resultsmentioning
confidence: 99%
“…7 Using UV/Vis with a surface roughness factor of 1.4, they calculated a density of 6.6 ð 10 13 molecules cm 2 for the parallel (ZnP4S) case and 17 ð 10 13 molecules cm 2 for the perpendicular (ZnP1S) case (Table 1). An STM image of a highly ordered adlayer of 5,10,15,20-tetrakis-(N-methylpyridinium-4-yl)-21H, 23H-porphyrin tetrakis-(ptoluenesulfonate) (TMPyP) on an iodine-coated gold surface in electrolyte solution was recorded by Kunitake et al 12,21 This side-by-side TMPyP arrangement has a surface concentration of 3.7 ð 10 13 molecules cm 2 (Table 1). 12 All of the parallel densities are within a factor of 3, whereas there is an order of magnitude spread for the perpendicular densities of porphyrin surface concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…67 In this study, we found for the first time that TMPyP forms highly ordered molecular arrays via self-ordering on an iodine-modified Au(111) electrode in 0.1M HClO 4 . 67 In a high-resolution image, the flat-lying TMPyP molecule is visible as a square with four bright spots.…”
Section: Sulfate/bisulfate Adlayersmentioning
confidence: 68%
“…67 In this study, we found for the first time that TMPyP forms highly ordered molecular arrays via self-ordering on an iodine-modified Au(111) electrode in 0.1M HClO 4 . 67 In a high-resolution image, the flat-lying TMPyP molecule is visible as a square with four bright spots. The center-to-center distance between the bright spots, measured diagonally, was 1.3 nm, which is nearly equal to the distance between two pyridinium units, measured diagonally.…”
Section: Sulfate/bisulfate Adlayersmentioning
confidence: 68%
See 1 more Smart Citation